INTERNSHIP TRAINING IN ACCOUNTING. - Miller, Herbert E. (The Accounting Review, 1945)
Abstract Internship programs are so well established in some of the professions that it is probably unnecessary to devote any effort to the definition of terms. Very broadly, the author looks upon internship training in accounting as an arrangement, which enables the accounting student to achieve some degree of blending of experience with classroom training. This is in contrast with the more usual situation in which the classroom environment precedes an exposure to accounting practice. Accounting internships, in the sense used here, are not a recent development. For some time now, a number of schools have had established programs which permit, and even encourage, accounting majors to spend some time with an accounting firm before obtaining their college degrees. In some instances industrial firms are included in this type of arrangement. In fact, there are many variations of internship programs. In setting forth some of the prospective benefits obtainable from internship training in accounting, most of the discussion in the article refers to public accounting firms.